2015
DOI: 10.1002/app.42932
|View full text |Cite
|
Sign up to set email alerts
|

Flame retarding mechanism of Polyamide 6 with phosphorus‐nitrogen flame retardant and DOPO derivatives

Abstract: A novel flame-retardant composite was prepared by introducing a phosphorus-nitrogen flame retardant and DOPO-SiO 2 into PA6. DOPO-SiO 2 was synthesized successfully in a one-step process. PA6/OP1314/DOPO-SiO 2 achieved a UL 94 V-0 rating with an LOI value of 31%. The maximum mass loss rate of decomposition decreased significantly and char residue increased to 11.6 wt % compared with that of pure PA6. The compacted and dense char was formed due to the combination of the P-N flame retardant and DOPOSiO 2 . The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
2
25
0
1
Order By: Relevance
“…The maximum mass loss rate is similar with 2.05%/°C. This has already be shown in the literature . At 650°C, a residue of 3.44% remained (Figure ).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The maximum mass loss rate is similar with 2.05%/°C. This has already be shown in the literature . At 650°C, a residue of 3.44% remained (Figure ).…”
Section: Resultssupporting
confidence: 84%
“…However, only introducing the FR cannot eliminate the melt dripping behavior. Further information and preliminary work can be found elsewhere . The hBN is platelet‐shaped with an average particle size of approximately 15 μm.…”
Section: Methodsmentioning
confidence: 99%
“…The flame of the spline went out after nearly 8.2 s during the second test. As our previous research showed, OP1314 can release diethylphosphinic acid acting as the chain‐terminating agent during the decomposition process . Thus, the sample with OP1314 could self‐extinguish in a short time, which resulted in the increasing of the LOI value.…”
Section: Resultsmentioning
confidence: 91%
“…With the LOI value of 23%, neat PA6 was easy to burn in air with continuous flaming drippings and without self‐extinguishing. Exolit OP1314 was a universal non‐halogen flame‐retardant for polyamides, with the addition of 12 wt % OP1314 added, the LOI value has a significant increase to 28.0% and the flame extinguished in 2.5 s without drippings after the first combustion test. Unfortunately, some burning melt‐droplets dripped and ignited the absorbent cotton under the spline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation